Pengaruh Kualitas Pelayanan, Good Coorporate Governance Dan Strategi Pemasaran Terhadap Loyalitas Nasabah (Studi Kasus Pada Bank Sumut Syariah Cabang Pembantu Simpang Kayu Besar) - Prayogi, Bayu; Rokan, Mustafa Khamal (Universitas Labuhanbatu, 2022)
Quality of service, Good Corporate Governance and a good and good marketing strategy from a bank will of course have an impact on the loyalty of customers who save and use products from the bank, if the customer becomes satisfied it will automatically have an impact on loyalty and establish a long-term relationship with the bank. This study wants to prove the effect of each variable, namely service quality, Good Corporate Governance and Marketing Strategy as on loyalty to customers of Bank Sumut Syariah Simpang Kayu Besar Sub-Branch. Based on previous research and related to supporting theories put forward by experts using the SPSS program as a statistical data processing tool. This type of research is explanatory research which intends to provide an explanation of causality between variables. In this study, the researcher used a non-probability sampling technique, that is, each element in the population does not have the same probability of becoming a sample. While the sampling technique used in this research is purposive sampling. While the population that is used as a sample is 30 debtors, with data analysis techniques using path analysis. Based on data processing using path analysis, it is proven that service quality has an effect on customer loyalty, Good Corporate Governance has no effect on customer loyalty and marketing strategy has a positive and significant effect on customer loyalty.